2004
DOI: 10.1590/s0004-28032004000100013
|View full text |Cite
|
Sign up to set email alerts
|

Proposta de questionário para caracterização da prevalência de sintomas digestivos nas doenças difusas do tecido conjuntivo

Abstract: The connective tissue diseases are usual causes of many gastrointestinal complaints. The use of an interview plus predefined questionnaire seems a very effective way to identify and characterize symptoms and is even sometimes able to uncover features unknown before. Finally, the lack of studies, specially updated studies, did not allow more comprehensive comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…regurgitation, heartburn, nausea, vomiting, abdominal distension and pain in the upper abdominal region. [8][9][10][11][12][13] Despite this diversity of digestive symptoms, there are currently no studies analyzing the possible anatomical alterations found in the upper gastrointestinal tract of patients with DM. In cases of juvenile DM, vascular abnormalities in gastroduodenal mucosa, as well as bioelectric activity of gastric muscles, have been described.…”
Section: ■ Resultsmentioning
confidence: 99%
“…regurgitation, heartburn, nausea, vomiting, abdominal distension and pain in the upper abdominal region. [8][9][10][11][12][13] Despite this diversity of digestive symptoms, there are currently no studies analyzing the possible anatomical alterations found in the upper gastrointestinal tract of patients with DM. In cases of juvenile DM, vascular abnormalities in gastroduodenal mucosa, as well as bioelectric activity of gastric muscles, have been described.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Underlying vasculitis was demonstrated in 50% of them. 2,3,4,5,6 The vasculitis usually affects small vessels of the intestinal wall. The histological assessment demonstrates atrophy and degeneration of the media, fibrinoid necrosis, thrombosis and lymphocytic infiltrate in lamina propria; the immunohistochemical analysis shows deposit of immune complexes, complement and fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal tract vasculitis is almost always accompanied by activity in other organs, such as skin, kidneys and CNS. 2,3,4,5 PI is usually asymptomatic; however, the cysts can rupture and cause pneumoperitoneum. 1,9,10 There seems to be an association between new leukopenia and thrombocytopenia or worsening of the pre-existing leukopenia with intestinal vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As alterações provocadas no trato gastrintestinal, embora dependam do tipo de doença difusa do tecido conjuntivo, podem conduzir à desnutrição, uma vez que interferem na ingestão e absorção dos nutrientes (MACHADO et al, 2004). Dentre essas alterações, pode-se citar: anormalidades da cavidade oral, como limitação na abertura da boca (por alteração da articulação temporomandibular), dor ao mastigar e dificuldade de deglutição, seja por complicações da própria doença reumática ou como conseqüência da Síndrome de Sjogren; disfunção esofagiana com disfagia ou odinofagia, má absorção e enteropatia perdedora de proteínas (GALPERIN; GERMAN; GERSHEIN, 2003).…”
Section: Introductionunclassified